Social Media Addiction in The Young Community: Elucidation of The Development of Behavioral Responses - Zainab, Yasmeen; Ajmal, Noor Fatima; Iqbal , Hina (Universitas Ahmad Dahlan, 2023)
Background: University students have been using social media in an uncontrolled manner without knowledge of the negative impacts on their cognitive functionality. Therefore, an assessment of the alterations in the behavior pattern of the university students is required to associate the linkage between social media use and subsequent aggressiveness. Contribution: Current work has for the first time conducted a socio-behavioral study on the younger university students for gaining an insight into their inclination towards using different social media platforms and changes in their behavioral patterns. Method: University students (73 total; 35 males and 38 females) were chosen who had history of using social media for the last three to five years. These students were affiliated with higher education institutions in Pakistan and the time of analysis was September 2022 – January 2023. An open-ended questionnaire was filled and statistically analyzed for significance using Origin software and SPSS software Results: This work has identified significant relationship between the social media utilization and alterations in the behavior of university students. Different determinants worked upon in this research are the impacts of the social media on cognitive occupation, emotive functions, relapse, conflict, anger, and hostility. Conclusion: The study has associated and evaluated such behavioral factors as determinants of aggression in the younger generation. Also, the study has compared and contrasted the appearance of aggression as a pattern taking in consideration different gender roles to comprehend the role of gender in perceiving and adopting social media trends.